A professionalisation programme towards children's risk-taking in play in childcare contexts: moral friction on developing attitudes and collegial expectations - van Rooijen, Martin; Jacobs, Gaby (European early childhood education research journal, 2019)
Interest in the professionalisation of childcare workers is growing, as the responsibility for children's upbringing and development is extended from the family area to early childhood education and care institutions. This sector is subject to intensified guidelines, where the overprotective tendency in society towards children has resulted in diminished possibilities to engage in risky play. This creates dilemmas for professionals in making clear decisions, balancing between protection and facilitating challenging play situations. This paper investigates the impact of a professional development programme developed and delivered by the main author on facilitating children's risky play in seven Dutch after-school childcare settings. A qualitative study was conducted to examine moral values and dilemmas emerging in this context. Moral frictions centred around 'safety and autonomy' in the work with children, and 'unity and diversity' in collaborating with colleagues.